PENGELOLAAN SAMPAH DI PASAR BARU KARAWANG SEBAGAI UPAYA PELESTARIAN LINGKUNGAN BERDASARKAN PERDA KABUPATEN KARAWANG NO. 9 TAHUN 2017 TENTANG PENGELOLAAN SAMPAH - Aris Santoso; Margo Hadi Pura (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Waste Management at Pasar Baru Karawang. Department of Law, Singapore University, Karawang. This research aims to understand the waste management process in Pasar Baru in Karawang, by looking at the Government's efforts to manage waste in Pasar Baru and also the role of the community in managing waste in the area. This type of research is a qualitative approach. the origin of the information used is the main information and inferior information. The main information is the Head of the UPTD Cleanliness Bureau of the Living Area and Cleanliness of the Karawang Regency, the janitor, as well as the tradesmen in the latest Karawang market, on the other hand, the secondary information is the legislation. The instruments used in this research are researchers and questions and answers, and the methods of collecting information include: Monitoring, Questioning and Selection. From the results of research that has been tried, it is stated that 1) The method of waste management in Pasar Baru Karawang does not practice waste selection, the waste is only collected by market traders and cleaning officers then carried by cleaning officers using motorized carts to trucks and containers or directly carried using truck fleet. 2) The government's effort in managing waste around the market is by using the method of transporting dirty every day to avoid dirty hoarding and following the local sub-district cleaning officers to help remove the trash in the Karawang Market. 3) Citizens' participation in waste management at Pasar Baru Karawang is a method of cleaning and accumulating garbage near the area after that put the garbage into a sack so that it makes it easier for officers to transport it and obediently pay fees for sales services and services every day Rp. 5000 / day. Therefore, this research aims to identify, analyze, and find the best solution regarding the problem of existing waste in creating a clean and healthy market environment and creating comfort in commercial activities carried out by the market community, especially in Pasar Baru Karawang.